Transcultural encounters between Germany and India : kindred spirits in the nineteenth and twentieth centuries /: kindred spirits in the nineteenth and twentieth centuries. (2014) - Cho, Joanne Miyang, 1959-; Kurlander, Eric, 1973-; McGetchin, Douglas T
No abstract available